2020
DOI: 10.1007/s10450-020-00271-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of resorcinol–formaldehyde hydrogel as adsorbent for cesium ion

Abstract: We evaluated the performance of a resorcinol-formaldehyde (RF) hydrogel as an adsorbent for removing aqueous cesium ions (Cs + ), by synthesizing cylindrical pellets of RF gels under different molar ratios (R/C) between resorcinol (R) and sodium carbonate (C) as the catalyst for the sol-gel polycondensation in the range from 2.5 to 400. The RF gel prepared at R/C = 2.5, containing the greatest amount of sodium ion (Na + ), had the greatest Cs + adsorption amount (0.660 mmol g −1 ), because Cs + could be adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The diffusion coefficients obtained for AAC and SAC cryogels was found in the range of 1.01 × 10 −9 −8.81 × 10 −10 m 2 s −1 and depends on the composition, cross-linking percentage, and ionic strength of the immersion solution. Taguchi et al 28 synthesized resorcinol−formaldehyde hydrogel with various resorcinol (R) (main monomer) and sodium carbonate (C) (reaction catalyst) ratios for cesium uptake. It was found that, when the R/C ratio (mol/mol) was 2.5, the diffusion coefficient was 1.45 × 10 −12 m 2 s −1 , while with increase of the R/C ratio, the diffusion coefficient increased and reached 7.11 × 10 −12 m 2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion coefficients obtained for AAC and SAC cryogels was found in the range of 1.01 × 10 −9 −8.81 × 10 −10 m 2 s −1 and depends on the composition, cross-linking percentage, and ionic strength of the immersion solution. Taguchi et al 28 synthesized resorcinol−formaldehyde hydrogel with various resorcinol (R) (main monomer) and sodium carbonate (C) (reaction catalyst) ratios for cesium uptake. It was found that, when the R/C ratio (mol/mol) was 2.5, the diffusion coefficient was 1.45 × 10 −12 m 2 s −1 , while with increase of the R/C ratio, the diffusion coefficient increased and reached 7.11 × 10 −12 m 2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Typical adsorbents such as activated carbons (AC), natural zeolites, and clays have been used, but they are often characterized by low adsorption capacities or the need to be chemically treated to acquire desirable adsorption properties. Natural sorbents like zeolites and AC usually show low removal capacities in the ranges of 1.3–10 mg/g for Sr 2+ ions and 0.7–51 mg g −1 for Cs + . Synthetic polymers like hydrogels and cryogels can reach much higher removal capacities, up to 312 mg g −1 for Sr 2+ and 420 mg g −1 for Cs + ions. ,, A list of literature works investigating Cs + and Sr 2+ ions adsorption from aqueous media onto different sorbents is reported in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to obtain new properties for the RFR by changing the initial components while preparing the resorcinol–formaldehyde (RF) polymer gel. Taguchi et al [ 18 ] synthesized the resorcinol–formaldehyde (RF) hydrogel with a different ratio between resorcinol and sodium carbonate (R/C) serving as a catalyst for the polymerization reaction. The authors concluded that along with the increase in the R/C ratio, the hydrogel absorption capacity decreases, and the rate of the ion exchange process, on the contrary, increases.…”
Section: Introductionmentioning
confidence: 99%